The consulting project cycle - Markham, Calvert (Henry Stewart Talks, 2015)
Skills needed in consulting projects, Importance of first impressions, Consultant thinking vs. Client thinking, Time management, Setting up a project (Possible starting points), Tools for analysis a situation & assessing readiness for change, Dealing with uncertainty & resistance, Capturing benefits from closure